Differential acute postprandial effects of processed meat and isocaloric vegan meals on the gastrointestinal hormone response in subjects suffering from type 2 diabetes and healthy controls: a randomized crossover study - Belinova, Lenka; Kahleova, Hana; Malinska, Hana; Topolcan, Ondrej; Vrzalova, Jindra; Oliyarnyk, Olena; Kazdova, Ludmila; Hill, Martin; Pelikanova, Terezie (PloS one, 2014)
BACKGROUND: The intake of meat, particularly processed meat, is a dietary risk factor for diabetes. Meat intake impairs insulin sensitivity and leads to increased oxidative stress. However, its effect on postprandial gastrointestinal hormone (GIH) secretion is unclear. We aimed to investigate the acute effects of two standardized isocaloric meals: a processed hamburger meat meal rich in protein and saturated fat (M-meal) and a vegan meal rich in carbohydrates (V-meal). We hypothesized that the meat meal would lead to abnormal postprandial increases in plasma lipids and oxidative stress markers and impaired GIH responses. METHODS: In a randomized crossover study, 50 patients suffering from type 2 diabetes (T2D) and 50 healthy subjects underwent two 3-h meal tolerance tests. For statistical analyses, repeated-measures ANOVA was performed. RESULTS: The M-meal resulted in a higher postprandial increase in lipids in both groups (p<0.001) and persistent postprandial hyperinsulinemia in patients with diabetes (p<0.001). The plasma glucose levels were significantly higher after the V-meal only at the peak level. The plasma concentrations of glucose-dependent insulinotropic peptide (GIP), peptide tyrosine-tyrosine (PYY) and pancreatic polypeptide (PP) were higher (p<0.05, p<0.001, p<0.001, respectively) and the ghrelin concentration was lower (p<0.001) after the M-meal in healthy subjects. In contrast, the concentrations of GIP, PYY and PP were significantly lower after the M-meal in T2D patients (p<0.001). Compared with the V-meal, the M-meal was associated with a larger increase in lipoperoxidation in T2D patients (p<0.05). CONCLUSION/INTERPRETATION: Our results suggest that the diet composition and the energy content, rather than the carbohydrate count, should be important considerations for dietary management and demonstrate that processed meat consumption is accompanied by impaired GIH responses and increased oxidative stress marker levels in diabetic patients. TRIAL REGISTRATION: ClinicalTrials.gov NCT01572402.
Keywords: Gastrointestinal Hormones; Triglycerides; glukagonu podobný peptid 1; Glucagon-Like Peptide 1; dieta veganská; krevní glukóza; Insulin; lipidy; Postprandial Period; Meat; Humans; triglyceridy; Ghrelin; lidé středního věku; Female; Middle Aged; Food Handling; postprandiální období; Gastric Inhibitory Polypeptide; Male; Diabetes Mellitus, Type 2; manipulace s potravinami; ghrelin; ženské pohlaví; Lipids; diabetes mellitus 2. typu; žaludeční inhibiční polypeptid; gastrointestinální hormony; Diet, Vegan; maso; Blood Glucose; inzulin; lidé; mužské pohlaví